Endophthalmitis Following XEN Stent Exposure. Issue 10 (October 2018) - Karri, Bhavani; Gupta, Chandni; Mathews, Divya
Abstract : Backround: XEN45 Gel stents are in their infancy, and clinical expertise with microsurgical glaucoma devices are increasing. The soft flexible nature of the XEN stent together with its malleability under the conjunctival tissue should negate any risk of exposure of the XEN45 stent (XEN). However, we report a case in which sight-threatening endophthalmitis was the presenting feature of this complication. Case Report: We present a case of uncomplicated XEN implantation that developed endophthalmitis 4 months after surgery. She gave an 8-day history of diarrhea before presentation. She was noted to have exposure of the XEN stent at the point of entry of the XEN into the subconjunctival space. The stent was removed, pars plana vitrectomy was carried out, and intravitreal antibiotics were administered. Achieving low intraocular pressures, bearing in mind her preservative allergy, became a challenge, as we struggled to manage her advanced glaucoma medically. A CyPass Micro-Stent was subsequently inserted to control the intraocular pressure. Conclusions: Episodes of XEN stent exposure may not be so isolated. We postulate that poor handwashing transmitted the causative organism to the exposed stent, which then resulted in endopthalmitis. We would like to highlight a few learning points from this case.